A cost-effectiveness analysis of standard versus endovascular abdominal aortic aneurysm repair - Forbes, Thomas L. (Canadian Medical Association, 2002)
OBJECTIVE: To compare endovascular and standard open repair of abdominal aortic aneurysms in terms of initial in-hospital costs and the costs of secondary interventions and surveillance. DESIGN: A retrospective study. SETTING: A university-affiliated tertiary care medical centre. PATIENTS: Seven patients who underwent elective endovascular (EV) repair of an abdominal aortic aneurysm in 1998 and 31 patients anatomically suitable for endovascular repair who underwent standard (STAN) elective repair. Follow-up ranged from 2 to 14 months. INTERVENTIONS: Elective repair of an abdominal aortic aneurysm with use of the standard technique or endovascular technology. OUTCOME MEASURES: Costs common to both groups were not determined. Costs were determined for total hospital stay, preoperative or postoperative embolization, grafts, additional endovascular equipment, and follow-up computed tomography. RESULTS: Groups were similar with respect to demographic data and aneurysm size (EV = 6.23 cm v. STAN = 6.05 cm). All patients were in American Society of Anesthesiologists class III or IV. Vanguard bifurcated grafts and extensions were used in the EV group. The total cost for both groups in Canadian dollars included: cost of stay (EV, 5.6 d, $2092.63 v. STAN, 10.7 d, $4449.19; p = 0.009); cost of embolization (EV, n = 3; $900/procedure); cost of follow-up CT (EV, 5.4 per patient; $450/CT); cost of grafts (EV = $8571.43, STAN = $374); additional radiologic equipment costs (EV = $1475). The mean total cost differed significantly between the 2 groups (EV = $14 967.63 v. STAN = $4823.19; p = 0.004). The additional cost associated with a reduction in hospital stay was calculated by determining the incremental cost-effectiveness ratio (ICER: difference in mean costs/difference in mean length of stay = $1604.51). CONCLUSIONS: Endovascular repair continues to be more expensive than standard open repair determined according to procedural and follow-up costs. The technology is still in the developmental stage, but as it evolves and follow-up protocols are streamlined, it is hoped that there will be an eventual reduction in the costs associated with the endovascular procedure.